2020
DOI: 10.1038/s41598-020-68487-0
|View full text |Cite
|
Sign up to set email alerts
|

Variations in foliar carbon:nitrogen and nitrogen:phosphorus ratios under global change: a meta-analysis of experimental field studies

Abstract: foliar-level stoichiometry plays an important role in ecosystem elemental cycling. Shifts in foliar ratios of carbon to nitrogen (c:n) and nitrogen to phosphorus (n:p) in response to global change can therefore have a large impact upon ecosystem function. We conducted a meta-analysis with 2,236 paired observations from 123 published studies to investigate the responses of foliar C:N and N:P ratios to experimental global change treatments, i.e. warming, increased precipitation, drought, n addition and elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Our study revealed that R− significantly decreased the C:P ratios of leaves and soils, but R+ increased them (Figure 2). It is widely accepted that C is linked to biological processes, such as photosynthesis and C allocation (Pausch & Kuzyakov, 2018; Rivas‐Ubach et al., 2012), whereas P depends on fewer biological mechanisms, but has a greater dependence on the initial P content of bedrock and land development processes (Peñuelas et al., 2013; Xu et al., 2020). Thus, changes in C rather than P under changes in precipitation might be responsible for the significant variations in the C:P ratios of leaves and soil.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that R− significantly decreased the C:P ratios of leaves and soils, but R+ increased them (Figure 2). It is widely accepted that C is linked to biological processes, such as photosynthesis and C allocation (Pausch & Kuzyakov, 2018; Rivas‐Ubach et al., 2012), whereas P depends on fewer biological mechanisms, but has a greater dependence on the initial P content of bedrock and land development processes (Peñuelas et al., 2013; Xu et al., 2020). Thus, changes in C rather than P under changes in precipitation might be responsible for the significant variations in the C:P ratios of leaves and soil.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of anthropic fertilization and the arrival of invasive species in other areas can substantially alter previously pristine areas by altering soil biogeochemical cycles. Associated impacts will not only affect biodiversity or landscapes but will also greatly affect biogeochemical cycles and ecological stoichiometry (Cusak et al, 2016; Sardans, Grau, et al, 2017; Wang et al, 2017; Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The soil had richer N supply capacity at shady slope than that in sunny slope. Soil N:P ratio was an important indicator of N nutrient availability, and it was usually influenced by environmental factors and soil properties in forest ecosystems [26,[40][41][42]. In our research, soil N:P ratios ranged from 2.79 to 4.61 in sunny slope and from 3.01 to 9.24 in shady slope, respectively.…”
Section: Decoupling Of Soil C:n:p Stoichiometry In Shady Slopementioning
confidence: 55%
“…In detail, soil acidity usually inhibits microbial activity and bacterial growth [24], mainly owing to the higher H+ concentration disrupting the permeability and stability of bacterial cell membranes [25]. P content is mainly related to habitat conditions and soil lithology [26]. During the field sampling, we found no significant difference in soil texture between the two slopes.…”
Section: Altitudinal Patterns In Soil C N and P Contents At Sunny And Shady Slope Aspectsmentioning
confidence: 71%